(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: This article explores the Creative Approach to Language Teaching (CALT), a methodology developed and successfully implemented at Masaryk University Language Centre. The approach recognizes students’ existing knowledge and diverse skills, encouraging their active contributions to language learning. By emphasizing creativity as an innate skill, it engages learners in real-life communication scenarios, fostering problem-solving, collaboration, and self-expression. The article also discusses the advantages of student-generated sources, highlighting how students can select learning materials, improve autonomy, and enhance critical thinking skills. This approach redefines the teacher’s role as a facilitator rather than a provider of knowledge, creating a dynamic and interactive learning environment.